An updated checklist of Psychidae (Lepidoptera) of Albania - Ana Nahirnić-Beshkova (Historia naturalis bulgarica)
The last checklist of Psychidae given in Arnscheid & Weidlich (2017) has been updated. Altogether 23 species of Psychidae are confirmed for the territory of Albania. Eochorica balcanica is excluded from the list, and Psyche casta and Reisseronia pusilella were found as new for the country during the field studies. New records for ten species are provided in the present study.